Aberrant DNA methyltransferase expression in pancreatic ductal adenocarcinoma development and progression - Gao, Jun (BioMed Central, 2013)
BACKGROUND: Altered gene methylation, regulated by DNA methyltransferases (DNMT) 1, 3a and 3b, contributes to tumorigenesis. However, the role of DNMT in pancreatic ductal adenocarcinoma (PDAC) remains unknown. METHODS: Expression of DNMT 1, 3a and 3b was detected in 88 Pancreatic ductal adenocarcinoma (PDAC) and 10 normal tissue samples by immunohistochemistry. Changes in cell viability, cell cycle distribution, and apoptosis of PDAC cell lines (Panc-1 and SW1990) were assessed after transfection with DNMT1 and 3b siRNA. Levels of CDKN1A, Bcl-2 and Bax mRNA were assessed by qRT-PCR, and methylation of the Bax gene promoter was assayed by methylation-specific PCR (MSP). RESULTS: DNMT1, 3a and 3b proteins were expressed in 46.6%, 23.9%, and 77.3% of PDAC tissues, respectively, but were not expressed in normal pancreatic tissues. There was a co-presence of DNMT3a and DNMT3b expression and an association of DNMT1 expression with alcohol consumption and poor overall survival. Moreover, knockdown of DNMT1 and DNMT3b expression significantly inhibited PDAC cell viability, decreased S-phase but increased G1-phase of the cell cycle, and induced apoptosis. Molecularly, expression of CDKN1A and Bax mRNA was upregulated, and the Bax gene promoter was demethylated. However, a synergistic effect of combined DNMT1 and 3b knockdown was not observed. CONCLUSION: Expression of DNMT1, 3a and 3b proteins is increased in PDAC tissues, and DNMT1 expression is associated with poor prognosis of patients. Knockdown of DNMT1 and 3b expression arrests tumor cells at the G1 phase of the cell cycle and induces apoptosis. The data suggest that DNMT knockdown may be a novel treatment strategy for PDAC.